Development of High Power Air-core Water-cooled Reactor - HE Duochang (Kongzhi Yu Xinxi Jishu)
High power air-core reactor can be used in high power converter and electricity power transport system to limit the shortcircuit current. This paper presented a high power reactor using air-core water-cooled, tightly winding and multi-winding packing technique which significantly improves the power density comparing to conventional reactor. The proposed reactor also applies the magnetic vector potential superposition methodology and epoxy casting technology, which not only solves the calculation of electromotive force of winding coil but also has greater current shock withstanding capability.